Reshoring from a demand-side perspective: Consumer reshoring sentiment and its market effects - Grappi, Silvia; Romani, Simona; Bagozzi, Richard P. (Journal of world business : JWB, 2018)
Reshoring is the company decision to relocate activities back to the home country. Our study complements the existing research in IB by adopting a demand-side perspective. We identify new, demand-based drivers for reshoring that integrate with the firm-based ones, thereby further informing the company decision process in this context. We develop a Consumer Reshoring Sentiment (CRS) scale through multiple studies conducted on consumers (total=1149) in two countries. Our findings reveal: six demand-based drivers that compose CRS; a link between CRS and consumer willingness to reward the reshoring company; and the effectiveness of CRS in segmenting and targeting the market.